The impact of economic policies on poverty and income distribution : evaluation techniques and tools - Bourguignon, François.; Pereira da Silva, Luiz A. (Washington, DC : Copublication of the World Bank and Oxford University Press, New York, 2003)
This book contains review techniques and tools that can be used to evaluate the poverty and distributional impact of economic policy choices. This title describes the most robust techniques and tools, from the simplest to the most complex, and aims to identify best practices. It also addresses an evaluation technique and its applications.
Includes index.
Includes bibliographical references (p. 369-395).
rua 12/06/17, ijb 07/02/2019
Loan
Keywords: Economic assistance; Poverty; Income distribution